Age and education level as factors associated with delayed diagnosis among female breast cancer patients - Athaya salsabila Harmono putri; Andi Siswandi; Muhammad Hatta; Aminuddin Ramadhan (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Cancer is a malignant disease caused by uncontrolled abnormal cell growth and is one of the leading causes of death worldwide. Breast cancer is a malignancy of breast tissue originating from the ductal or lobular epithelium and is the cancer with the highest incidence in women globally. Purpose: To determine factors of age and educational level influencing delayed diagnosis in female breast cancer patients Method: This study used an observational analytic study with a cross-sectional approach. A total of 52 respondents were included in the study, which influenced delayed diagnosis in women with breast cancer at Abdul Moeloek Hospital in 2025. Results: The results showed that the majority of respondents experienced delayed breast cancer diagnosis (27 respondents (51.9%), while 25 respondents (48.1%) did not experience delays, thus making delayed diagnosis still considered high. Bivariate analysis using Fisher's Exact Test showed that age significantly influenced delayed diagnosis (p = 0.011; OR = 5), with elderly women having a five-fold greater risk of experiencing delays compared to late adulthood. Furthermore, education level also significantly influenced the risk (p = 0.004). Conclusion: There is a relationship between age and education level, which influence late diagnosis in women with breast cancer.